2018
DOI: 10.1016/j.aca.2018.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide polymer labels for multiplexed determination of biomarkers in human serum samples by means of size exclusion chromatography-inductively coupled plasma mass spectrometry

Abstract: Lanthanide polymer-labelled antibodies were investigated to improve the analytical figures of merit of homogeneous immunoassays with inductively coupled plasma mass spectrometry (ICP-MS) detection for multiplexed biomarker analysis in human serum samples. Specific monoclonal antibodies against four cancer biomarkers (CEA, sErbB2, CA 15.3 and CA 125) were labelled with different polymer-based lanthanide group to increase the number of metal labels per binding site. After the immunoreaction of the biomarkers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
(27 reference statements)
1
17
0
1
Order By: Relevance
“…Within this context, single chelates [4], commercial polymers containing several lanthanide atoms covalently attached [5], metal nanoparticles (NPs) most commonly made of gold [6,7] with diameters in the order of 20-50 nm, and quantum dots (QDs) [8,9] have been successfully investigated as elemental labels. The use of labels with many atoms of a given metal per tag will allow high signal amplification, and thus, good sensitivity for detection of the corresponding biomolecule.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, single chelates [4], commercial polymers containing several lanthanide atoms covalently attached [5], metal nanoparticles (NPs) most commonly made of gold [6,7] with diameters in the order of 20-50 nm, and quantum dots (QDs) [8,9] have been successfully investigated as elemental labels. The use of labels with many atoms of a given metal per tag will allow high signal amplification, and thus, good sensitivity for detection of the corresponding biomolecule.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other immunoassays (ECLIA, FIA, CLIA, etc. ), the ICP-MS-based immunoassay has several unique advantages and the potential capability for multiplex analysis [22,23,34,35]. Although many studies have been reported for the ICP-MS-based immunoassay, these was no report of multiplex detection involve in standard evaluation and clinical sample detection with the guidance of CLSI documents [23].…”
Section: Discussionmentioning
confidence: 99%
“…The operation parameters of the ICP-MS analyzer are shown in Table 1. In order to eliminate the impact of some interference situations (such as salts and incomplete injection) on the test results, Rh 3+ , In 3+ , Tb 3+ , Ho 3+ and Re 3+ were selected as potential quality control elements according to previous reports [34]. In addition, the Eu-labeled CEA antibody and the Sm-labeled AFP antibody were tested 50 times to evaluate the imprecision (presented as relative standard deviation/coefficient of variation (CV)) of the analyzer.…”
Section: Evaluation Of the Icp-ms Analyzermentioning
confidence: 99%
“…These polymer tags bind up to 60~120 lanthanides per antibody and increased the final ICP-MS sensitivity. Perez et al 48 labeled specific monoclonal antibodies against four cancer biomarkers (CEA, sErbB2, CA 15.3 and CA 125) with different polymer-based lanthanides and separated, by size exclusion chromatography followed by ICP-MS detection, the antigen-antibody complex. The lanthanide loading in the polymer tag may be 30 times that of lanthanide-DOTA to improve the sensitivity and detection limit.…”
Section: Immunological Taggingmentioning
confidence: 99%